Genetic and peripheral biomarkers of comorbid posttraumatic stress disorder and traumatic brain injury: a systematic review - Cowansage, Kiriana; Nair, Reshmi; Lara-Ruiz, Jose M.; Berman, Daniel E.; Boyd, Courtney C.; Milligan, Tiffany L.; Kotzab, Daniel; Bellanti, Dawn M.; Shank, Lisa M.; Morgan, Maria A.; Smolenski, Derek J.; Babakhanyan, Ida; et al. (Frontiers in Neurology, 2025)
BackgroundPosttraumatic stress disorder (PTSD) commonly cooccurs with traumatic brain injury (TBI) in military populations and is a significant predictor of poor long-term outcomes; however, it is unclear to what extent specific biological variables are associated with comorbidity. This PROSPERO-registered systematic review evaluates the current body of literature on genetic and peripheral biomarkers associated with comorbid TBI and PTSD.MethodsSearches were conducted in four databases (PubMed, PsycInfo, PTSDPubs, Scopus). We included published studies examining differences in peripheral biomarkers among civilian, military, and veteran participants with both TBI and PTSD compared to those with TBI alone as well as, in some cases, PTSD alone and healthy controls. Data were extracted from included studies and evidence quality was assessed.ResultsOur final analysis included 16 studies, the majority of which were based on data from active duty military and veteran participants. The results suggest that multiple gene variants are likely to contribute to the cumulative risk of PTSD comorbid with TBI. An elevated circulating level of the pro-inflammatory cytokine IL-6 was the most consistently replicated blood-based indicator of comorbid illness, compared to mTBI alone.ConclusionSeveral genetic and protein markers of cellular injury and inflammation appear to be promising indicators of chronic pathology in comorbid TBI and PTSD. Additional research is needed to determine how such factors indicate, predict, and contribute to comorbidity and to what extent they represent viable targets for the development of novel diagnostic tools and therapeutic interventions.